Pengembangan LKPD Model Problem Based Learning Berorientasi pada Kemampuan Berpikir Kritis Siswa Kelas IX SMP - Sri Ulfa Insani (Departement of Mathematics Education, 2024)
This is development research with the aim of this research is to produce student worksheet with problem based learning model oriented to student’s critical thinking skills with has good validity and practicality. The development model used is ADDIE stand for analyze, design, develop, implement, and evaluate. This research is in SMP Negeri 37 Pekanbaru with research subjects were 35 students in class IX. In this research used non-test techniques with validation sheets and practicality sheets instruments. Based on the result of this research showed that the student worksheet was included in the very valid category with an average score = 4,53. Then the student worksheet included in the very practical category with an average score = 4,24.